The Leverage of Psychological Capital: A Conservation of Resources Theory Perspective - Tama, Heka Ria; Mansyriah, Huwaida Zahra; Djastuti, Indi; Rahardja, Edy (LifeSciFi, 2025)
This study aims to bridge the inconsistency found in previous research regarding the role of transformational leadership on employee performance by proposing a conceptual model derived from the perspective of Conservation of Resources (COR) Theory. The study involved 200 respondents who have worked for five years in a financial company located in Semarang City, Central Java. Statistical data analysis was conducted using Analysis Moment of Structural (AMOS) software. Empirical testing through the formulation of five hypotheses yielded significant and acceptable results. The main findings of this study highlight the crucial role of psychological capital, viewed through the lens of COR Theory, as an effective bridge that stimulates the influence of transformational leadership on enhancing employee performance. Therefore, companies are encouraged to allocate resources to develop and strengthen employees' psychological capital, which includes self-efficacy, hope, optimism, and resilience. This study confirms that psychological capital is a strategic asset that can be optimized to support the success of transformational leadership, ultimately contributing to improved productivity and the overall competitive advantage of employees.